Behind the Innovation-Firm Performance Link: A Theoretical Analysis with Applications To Empirical Studies (Economic and Political Thought, 2014)
There is a growing empirical literature investigating the relationshipbetween innovation activities of the firms and their ‘performance’. Thesefirm-level studies usually employ Heckmann’s methodology and go under thename of CDM models (after the initials of the authors of the classical 1998paper: Crepon, Duguet and Mairesse). The outcome of these studies is thatfirms that innovate more usually perform better, but there is a considerablevariation when it comes to the details of the results. The aim of this paper isto contribute to the methodology of such literature, firstly, by discussing thetheoretical foundations of the CDM models and thus shedding more light onthe hypotheses underlying them, and secondly by assessing the usefulness ofthe Community Innovation Survey (CIS) in this respect. Several theoreticalapproaches are invoked, including neoclassical economics, Porter’s frameworkand evolutionary economics. It is argued that the positive relationship betweeninnovation and performance is strongly backed by economic theory but thehypothetical mechanisms behind the link can vary. Investigating the natureof the connection is a promising line of future research and examining theparts of the CIS database that were largely neglected in CDM-type studiesto date can help resolve the puzzle.